Effect of Remedial Measures on Incidence and Awareness about Medication Errors in an Indian Tertiary Care Hospital - Ratnamraju, Vivek; Dhande, Priti (Journal of Pharmacy Practice and Community Medicine)
Background: Any medication reaching a patient has tendency to face errors, from point of procurement to its consumption. Often health-care professionals, being human, are inevitably bound to commit errors potentially causing medications to be fatal or ineffective to patients, unless they are made aware about them. Objectives: To assess the knowledge, attitude and practices of health-care personnel, identify and evaluate medication errors and also analyse effect of remedial measures on the same. Materials and Methods: Prospective interventional study involving 151 Resident doctors, 112 Nursing staff and 15 Pharmacists. Their knowledge, attitude and practices regarding medication errors was assessed using a pre-tested questionnaire before and after interventions. Medication errors were identified at all patient-care levels with simultaneous remedial measures for reducing them. Data was analysed using Chi-square test. Results: Knowledge about medication errors and practice of reporting them was significantly better among nurses as compared to resident doctors and pharmacists (p<0.001) where unawareness was a significant reason (p<0.001) behind under-reporting. Remedial measures were effective as evident by increased awareness of participants (p<0.001) and reduced number of medication errors in the hospital. Conclusion: Poor awareness went hand in hand with the number of medication errors identified in study population which improved after remedial measures.
Keywords: Medication errors; Knowledge; Attitude; Practice; Intervention; Awareness; Reporting.